Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Kompetensi Pedagogik Guru SMP - Endang Sri Darmayanti; Bunyamin Bunyamin; M Prayito (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze the influence of the principal’s transformational leadership on the pedagogical competencies of junior high school teachers. Teachers’ pedagogical competencies are a key factor in improving the quality of learning and education. One factor believed to influence the improvement of teachers’ pedagogical competencies is the principal’s transformational leadership. Transformational leadership emphasizes the principal’s ability to provide motivation, intellectual stimulation, individual attention, and foster a collaborative school culture to support teachers’ professional development. This study employs a quantitative approach with an ex post facto design. The study was conducted at junior high schools in Jepon Subdistrict, Blora Regency, involving 101 teachers as the research sample, selected using proportionate stratified random sampling from a total population of 136 teachers. Data collection utilized a questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics, normality tests, linearity tests, and simple regression analysis with the aid of SPSS software. The results of the study indicate that the principal’s transformational leadership has a positive and significant effect on teachers’ pedagogical competence, with a regression coefficient of 0.650 and a significance level of 0.000 (p < 0.05). A correlation coefficient of 0.603 indicates a fairly strong relationship between the two variables, while a coefficient of determination of 0.363 indicates that the principal’s transformational leadership contributes 36.3% to teachers’ pedagogical competence. These findings suggest that inspirational, supportive, and professional development-oriented leadership can foster continuous improvement in teachers’ pedagogical competence. Therefore, strengthening the principal’s transformational leadership is a key strategy for enhancing the quality of learning and education in schools. It is hoped that the results of this study will serve as a basis for schools to develop leadership models capable of effectively enhancing teacher professionalism and the quality of learning. Keywords: Transformational Leadership, Principal, Teacher Performance Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kepemimpinan transformasional kepala sekolah terhadap kompetensi pedagogik guru SMP. Kompetensi pedagogik guru merupakan salah satu faktor penting dalam meningkatkan kualitas pembelajaran dan mutu pendidikan. Salah satu faktor yang diduga berpengaruh terhadap peningkatan kompetensi pedagogik guru adalah kepemimpinan transformasional kepala sekolah. Kepemimpinan transformasional menekankan pada kemampuan kepala sekolah dalam memberikan motivasi, stimulasi intelektual, perhatian individual, dan membangun budaya sekolah yang kolaboratif untuk mendukung pengembangan profesional guru. Penelitian ini menggunakan pendekatan kuantitatif dengan desain ex post facto. Penelitian dilaksanakan pada SMP di Kecamatan Jepon Kabupaten Blora dengan melibatkan 101 guru sebagai sampel penelitian yang dipilih menggunakan teknik proportionate stratified random sampling dari total populasi sebanyak 136 guru. Teknik pengumpulan data menggunakan angket yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan statistik deskriptif, uji normalitas, uji linearitas, dan analisis regresi sederhana dengan bantuan program SPSS. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional kepala sekolah berpengaruh positif dan signifikan terhadap kompetensi pedagogik guru dengan nilai koefisien regresi sebesar 0.650 dan nilai signifikansi sebesar 0.000 (p < 0.05). Nilai koefisien korelasi sebesar 0.603 menunjukkan hubungan yang cukup kuat antara kedua variabel, sedangkan nilai koefisien determinasi sebesar 0.363 menunjukkan bahwa kepemimpinan transformasional kepala sekolah memberikan kontribusi sebesar 36,3% terhadap kompetensi pedagogik guru. Temuan ini menunjukkan bahwa kepemimpinan yang inspiratif, suportif, dan berorientasi pada pengembangan profesional mampu mendorong peningkatan kompetensi pedagogik guru secara berkelanjutan. Oleh karena itu, penguatan kepemimpinan transformasional kepala sekolah menjadi salah satu strategi penting dalam meningkatkan kualitas pembelajaran dan mutu pendidikan di sekolah. Hasil penelitian ini diharapkan dapat menjadi bahan pertimbangan bagi sekolah dalam mengembangkan pola kepemimpinan yang mampu meningkatkan profesionalisme guru dan mutu pembelajaran secara efektif. Kata kunci: Kepemimpinan Transformasional, Kepala Sekolah, Kinerja Guru